أثر نمط استعمالات الأراضي الحضرية على مرونة المدينة - دراسة حالة مدينة بوسعادة - - معيـــوف زهــــير (University of M'Sila, 2024)
في ظل الوضعيات السلبية لتغيّرات المناخ حظي مفهوم المرونة باهتمام الأكاديميين وصانعي السياسات على حد سواء لتحسين مرونة المدن. يحاول هذا البحث الاجابة على التساؤل التالي: الى أيّ مدى يمكن ان يُؤثر نمط التوزيع المكاني لاستعمالات الاراضي الحضرية على مستويات مرونة مدينة بوسعادة ؟. يفترض البحث ان تقييم مستويات مرونة مدينة بوسعادة يتضمن فحص مجموعة من المعايير لها صلة بعناصر البيئة الحضرية وان التحقيق في تصورات السكان المحليين حول اضطرابات الحصول على الخدمة يسمح برفع مستوى مرونة المدينة. وانه كلما توافرت احياء فئات الانسجة الحضرية (أ، ب، جـ، د) لمدينة بوسعادة على قيم عددية اعلى لسمات المرونة المكانية كلما توفرت قدرة التكيف المكاني للأحياء. اعتمد على المنهج الاستقرائي والطريقة التشاركية للتحقق من الفرضيات. اظهرت نتائج خريطة تقييم مستويات مرونة مدينة بوسعادة بناء على فحص مجموعة من المعايير أن الأحياء غير المرنة هي (الحمايد، الباطن، سيدي سليمان وميطر)، تطلب ذلك التحقيق في تصورات السكان المحليين حول اضطرابات الحصول على الخدمة للأحياء السكنية غير المرنة، حيث بينت نتائج التحقيق انها تفتقد الى مراكز الامن ومراكز التكفل الطبي اللذان يمثلان في نظر خبراء دلفي معيارين مهمين في رفع مستوى المرونة، مما يعزز من كفاءة صنع القرار. كما اظهرت نتائج التحليل المكاني لسمات المرونة المكانية من حيث الكثافة، ان أحياء فئة النسيج الحضري (ب، جـ، د) تتوفر على قدرة تكيف مكاني افضل من فئة النسيج الحضري (أ). من حيث التنوع، حصل حي القصر ضمن فئة النسيج الحضري (أ) وحي بلاتو للفئة (ب) درجة عالية من تنوع المرافق، منحهما قدرة تكيّف مكاني افضل من فئة النسيج الحضري (جـ، د). من حيث الاتصالية، اظهرت فئة النسيج الحضري (أ، ب) قدرة تكيف مكاني افضل من فئة النسيج الحضري (جـ، د). من حيث التكرارات، حصلت فئة النسيج الحضري (أ) على قيم منخفضة للمقاييس المدروسة: كثافة التقاطعات (D_e)، نسبة ربط-العقد (LNR) ونسبة العقد الموصولة (CNR)، بينما ارتفعت بشكل كبير بفئة النسيج الحضري (ب، جـ، د)، منحهم ذلك مستويات قدرة تكيف مكاني افضل. كانت الغاية من تقييم مستويات المرونة كقيمة اجمالية لإبراز قدرة مدينة بوسعادة على الاستجابة اثناء الصدمة. كما ان غاية كشف توافر السمات الاربعة للمرونة المكانية: الكثافة، التنوع، الاتصالية والتكرار، هو اظهار قدرة مدينة بوسعادة على التكيّف المكاني عبر مراحل نموها الحضري، من خلال ممارسات التخطيط وتدخلات التحسين الحضري على الاحياء السكنية. تم تلخيص نتائج هذه الدراسة في مجموعة من مبادئ التصميم الحضري التي يمكن ان تساعد عمل المصممين والمخططين في توجيه استعمالات الاراضي الحضرية بإظهار تلك السمات المكانية (الكثافة، التنوع، الاتصالية والتكرار) لتكوين اماكن بمدينة بوسعادة أكثر مرونة تظهر الكثير من القدرات على الاستجابة والتكيّف اثناء الاضطراب.
In the context of the negative climate change situations, the concept of resilience has received the attention of both academics and policymakers to improve the resilience of cities. So this research tries to answer the following question: To what extent can the spatial distribution pattern of urban land use affect the resilience levels of the city of Bou-Saâda? The research assumes that the assessment of resilience levels is a city of Bou-Saâda, including an examination of a set of criteria relevant to the elements of the urban environment. Investigating the perceptions of the local population about the troubles in accessing the service allows for a higher level of the city's resilience. The higher the numerical values of the spatial resilience characteristics of the urban tissues of the city of Bou-Saâda, the more spatial adaptation capacity is available for the living. In order to verify the hypotheses, an inductive and participatory method was used. Based on an examination of a set of criteria, the results of the assessment map of the resilience levels of the city of Bou-Saâda showed for non-resilient neighborhoods is: (Al-Hameyd, Al-Baten, Sidi Slimane and Maytar). It is important to investigate the perceptions of the local population about the disruption of access to services for non-resistant neighborhoods. The results of the investigation showed that they lacked the security centers and medical care centers that, in the view of Delphi experts, were important criteria in raising resilience, thus enhancing the efficiency of decision-making. The results of analysis a spatial resilience characteristics in terms of density, a residential neighborhoods for the urban tissue category (b, c, d) has a better spatial adaptation capacity than the urban tissue category (a), In terms of diversity, the Al-Qasr neighborhood in the urban tissue category (a) and the Plato neighborhood in the urban tissue category (b) received a high degree of diversity of facilities, giving them a better spatial adaptation capacity than the urban tissue category (c, d). In terms of connectivity, the urban tissue category (a, b) showed better spatial adaptation capacity than the urban tissue category (c, d), In terms of redundancies, the urban tissue category (a) obtained low values for measurements: Intersection density (D_e), Link-Node Ratio (LNR) and Connected Node Ratio (CNR), while the urban tissue category (b, c, d) increased significantly, giving those better spatial adjustment capacity levels. The purpose of assessing the levels of resilience was as a total value to demonstrate the ability of a city to respond during shock. The purpose of detecting the availability of the four spatial resilience characteristics (density, diversity, redundancy and connectivity) is to demonstrate the capacity of the City of Happy to adapt spatially through urban growth, through planning practices and urban improvement interventions on neighborhoods. The results of this study are summarized in a set of urban design principles. It could help designers and planners to direct urban land uses. Showing these spatial resilience characteristics (density, diversity, redundancy and connectivity), to create places in a city that can be more resilient, there are many capacities to respond and adapt during a disturbance.
Keywords: المرونة، استعمالات الارض الحضرية، النسيج الحضري، المرونة المكانية، بوسعادة.; Resilience; Urban Land Uses; Urban Tissue; Spatial Resilience; Bou-Saâda.